ANALYZING PERCEIVED LEADERSHIP STYLE IN RELATION WITH PERCEIVED WORK STRESS IN PT PLN (PERSERO) UNIT INDUK PEMBANGUNAN SULAWESI BAGIAN UTARA - Kananlua, Abigael L.; Pangemanan, Sifrid S.; Saerang, Regina T. (Universitas Sam Ratulangi, 2019)
A good leadership is important in every company in achieving the company’s goals. A good leadership also will affect the work performance of employees, if the leadership style applied by the leader is not in the right way, the employee will experience stress at work. This study aimed to determine what type of leadership style should be embraced to decrease the negative effects of stress on employees. Research uses a quantitative approach. The sample are 60 employees of PT PLN (Persero) Unit Induk Pembangunan Sulawesi Bagian Utara and using Multiple Linear Regression Analysis. The results shows that Transformational, Transactional, and Laissez-faire leadership style simultaneously influence Work Stress. The findings also revealed that the Transformational Leadership style and Laissez-faire Leadership Style have negative relationship but does not significant influence Work Stress. While, Transactional Leadership Style has positive relationship and significant influence Work Stress. As for the recommendation, the leader should maintain and improve more on transformational leadership style by giving more motivation, inspiring and give more attention to the employees since it can brings good effect and can decrease on employees’ stress level. Keywords: transformational leadership, transactional leadership, laissez-faire, work stress